YOUTUBE DAN KEBHINNEKAAN (Persepsi akademisi terhadap youtube sebagai media alternatif penyampai pesan kebhinnekaan) - Aji, Haryo Kusumo (Transformasi, 2017)
This research is motivated by the rise of negative news concerning the issue of SARA, radicalismand so on that spread in cyberspace. Social media becomes the easiest place to spread contentlike this because of the easy access given to share any posts. Youtube as the largest video-basedsocial media became one of the reference individuals to find information based on audio andvisual. An academic with his academic background has a certain perception of this youtubemedia in conveying the message of diversity.By using qualitative approach interpretive and case study method, hence got result of researchconducted by academics at Slamet Riyadi University. From the attention variables obtained thatsomeone's motive in watching youtube impressions is to know the clarity of an existinginformation, because of this media based on audio visual. While the external factor of thisvariable is the ease of using youtube to share in multi platform. For Interpretation variablesobtained that the value of the individual is in terms of usefulness using this medium is to increaseknowledge, also in the satisfaction as a place of entertainment. In the experience variables fromindividuals in the world of academics are for improving interest for pay attention to topicsrelated to education. Then, in the culture variables, namely religion and belief become the basisin perceiving a show that contains SARA issues. Individuals want to see how religion deals withemerging issues. Then, in the expectations variables shows how individual expectations tofurther multiply positive content in social media in order to muffle the negative content so thatthe diversity of the Indonesian nation more realized.Keyword: Youtube, Diversity, perception, academia, alternative media